Chronological outcomes of renal function after adrenalectomy in patients with primary aldosteronism across age groups - Ma, Yu; Tang, Xiaofeng; Ge, Qian; Xu, Jianzhong; Gao, Pingjin; Wang, Jiguang; Zhu, Limin (Frontiers in Endocrinology, 2024)
Background: Patients with primary aldosteronism present with renal function decline after unilateral adrenalectomies. Our study aimed to assess the evolution of renal function after adrenalectomy in patients with primary aldosteronism across different age groups and to identify risk factors for postoperative renal function deterioration.Methods: We included 210 patients with primary aldosteronism categorized into three age groups: <40, 40-60, and ≥60 years old. We followed up the patients for 1 month, 1 year, and 5 years after adrenalectomy to assess outcomes. Multivariate analyses were performed to identify predictors of renal function deterioration, and a univariate logistic regression analysis was used to assess the relationship between KCNJ5 mutation status and the decline in renal function.Results: Patients aged <40 years had a shorter duration of hypertension, higher preoperative diastolic blood pressure, and higher preoperative estimated glomerular filtration rate (eGFR) than did those in the other age groups. This group also exhibited the highest rate of complete clinical success, although there were no significant differences in complete biochemical success among age groups. Renal function declined in all three groups after adrenalectomy. However, changes in blood pressure and eGFR in the short-or long-term after adrenalectomy showed no significant differences among the three groups. Hypertension duration, preoperative systolic blood pressure (SBP), and plasma aldosterone concentration (PAC) were predictors of postoperative renal function deterioration. KCNJ5 wild-type status was significantly correlated with the occurrence of chronic kidney disease after adrenalectomy.Conclusions: Unilateral adrenalectomy demonstrates favorable biochemical and clinical outcomes in patients with primary aldosteronism, irrespective of age. Long-term eGFR decline is similar among the different age groups. KCNJ5 mutation exhibits a protective effect against the risk of chronic kidney disease after unilateral adrenalectomy.